2019
DOI: 10.3390/ijerph16050676
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Collaborative Platform for the Development of Community Interventions to Prevent Non-Communicable Diseases

Abstract: Chronic diseases, also known as non-communicable diseases (NCD) are one of the most important public health problems of our time. Many of these diseases can be reduced by achieving healthy lifestyles. Community interventions are very useful in reducing these types of diseases since they have a direct impact over daily conditions and are adjustable to the complex situations that they carry. This article describes the process of the creation of a collaborative platform for the design and implementation of commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…On the other hand, the results of a review showed that there has been no comprehensive conceptual framework for ISC, and that each program requires specific mechanisms ( 70 ). For example, Del Busto et al developed a collaborative platform for the design and implementation of community interventions to prevent NCDs ( 19 ). New applications were suggested for the Collaborative Value Creation Framework for discovering leverage ( 71 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the results of a review showed that there has been no comprehensive conceptual framework for ISC, and that each program requires specific mechanisms ( 70 ). For example, Del Busto et al developed a collaborative platform for the design and implementation of community interventions to prevent NCDs ( 19 ). New applications were suggested for the Collaborative Value Creation Framework for discovering leverage ( 71 ).…”
Section: Resultsmentioning
confidence: 99%
“…Intersectoral initiatives may sometimes be designed to achieve health benefits and sometimes to achieve economic and social goals ( 18 ). Building effective relationships requires attention to the organizational differences between the sectors involved, the complexity and variability of contexts ( 19 ), and the core elements of partnership processes, including effective leadership and trust among partners ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature indicates that policy plans are more likely to be implemented effectively if they are developed and implemented in collaboration with a full range of partners who can significantly contribute to implementation from both within and outside the health sector (WHO 2013 :33). Therefore, to ensure successful implementation of policies for the prevention and control of NCDs, Del Busto and colleagues ( 2019 :9) posit that collaboration is significant and that governments must develop collaborative work between various stakeholders at different levels, both from within and outside the health sector.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle-related factors are the dominant causes of becoming overweight or obese, besides ageing of the population, genetic predisposition, and medical treatment [ 6 , 7 ]. Both overweight and obesity can be prevented and reduced by adopting a healthier lifestyle [ 8 ]. Lifestyle interventions are efficient and safe strategies to manage obesity.…”
Section: Introductionmentioning
confidence: 99%